Assessment of isokinetic knee strength in elite young female basketball players: correlation with vertical jump - Rouis, M.; Coudrat, L.; Jaafar, H.; Filliard, J.-R.; Vandewalle, H.; Barthelemy, Y.; Driss, T. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: To explore the isokinetic concentric strength of the knee muscle groups, and the relationship between the isokinetic knee extensors strength and the vertical jump performance in young elite female basketball players.